Research progress of moxibustion in the treatment of primary dysmenorrhea (艾灸治疗原发性痛经的研究进展) - YANG Man (杨曼); LU Ying (卢英); WANG Xuejing (王雪静) (中西医结合护理)
Moxibustion has been widely used in primary dysmenorrhea, and has the advantages of quick effect, obvious pain relief, and few side effects and adverse reactions. This paper reviewed the clinical and experimental research literatures of moxibustion in the treatment of primary dysmenorrhea, discussed the current research status of Traditional Chinese Medicine in the treatment of primary dysmenorrhea from the aspects of the law of point selection and the mechanism of action, and explored the clinical efficacy and further practice of moxibustion in the treatment of primary dysmenorrhea. (艾灸现已经广泛应用于原发性痛经(PD)治疗中, 具有见效快、止痛明显并且不良反应少的优点。本研究从选穴规律、作用机制等方面探讨中医在治疗PD的研究现状, 为进一步临床推广提供参考。)